Tropospheric nitrogen dioxide levels vary diurnally in Asian cities - Junsung Park; Hyunkee Hong; Hanlim Lee; Si-Wan Kim; Jhoon Kim; Michel Van Roozendael; Caroline Fayt; Myong-Hwan Ahn; Daniel J. Jacob; Seunghwan Seo; Kyoung-Min Kim; Daewon Kim; et al. (Communications Earth & Environment, 2025)
Abstract Satellite measurements of nitrogen dioxide have been used to infer nitrogen oxide emissions, a critical component in tropospheric chemistry and pollution. New observations from the Geostationary Environmental Monitoring Spectrometer offer a breakthrough by providing a daytime record of nitrogen dioxide over Asia. Here we present the summertime diurnal patterns of nitrogen dioxide at major cities, power plant regions, and the Strait of Malacca. The Geostationary Environmental Monitoring Spectrometer data across various regions show high nitrogen dioxide in the morning which decrease in the afternoon, with varying hourly peaks, troughs, and amplitudes reflecting diurnal characteristics of local emissions and chemistry. Nitrogen oxide emissions inferred from Geostationary Environmental Monitoring Spectrometer and the Weather Research and Forecasting model coupled with Chemistry also show distinct patterns among regions: early morning peaks occur over Hanoi, Guangzhou, and Bangkok; mid-to-late morning peaks appear over Seoul and Beijing; and late afternoon peaks are noted in the Yangtze River Delta region. Top-down emissions incorporating temporal changes in the Geostationary Environmental Monitoring Spectrometer nitrogen dioxide yield the most accurate nitrogen dioxide simulations.